2022
DOI: 10.3390/land11111879
|View full text |Cite
|
Sign up to set email alerts
|

On the Landscape Activity Measure Coupling Ecological Index and Public Vitality Index of UGI: The Case Study of Zhongshan, China

Abstract: In the context of high-quality urban development and the increasingly important role of urban green infrastructure (UGI) in public life, landscape activity (LA) has gradually become a dominant indicator for improving UGI quality and efficiency, as well as optimizing its environmental friendliness and meeting the recreational needs of the public. Relevant studies have shown that the ecological index (EI) and the public vitality index (PVI) can characterize LA from the perspectives of greening quality and public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…(2) The impact of road construction on the connectivity of ecological networks. In previous studies, scholars have been more concerned about the impact of human activities and the expansion of construction land on animal habitats [71,72], with more attention paid to the increase in the size and number of construction land patches. This study found that the rapid expansion of the transportation network system in recent years has blocked ecological patches.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The impact of road construction on the connectivity of ecological networks. In previous studies, scholars have been more concerned about the impact of human activities and the expansion of construction land on animal habitats [71,72], with more attention paid to the increase in the size and number of construction land patches. This study found that the rapid expansion of the transportation network system in recent years has blocked ecological patches.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the main focus for the travel vitality index is between the vitality index and the ecological index (Zhang et al, 2022). Some scholars have laid the groundwork for a quantitative exploration of community street vitality by integrating streets into a single vitality index to highlight their social characteristics (Liu et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%